Analisis Kebijakan Kabupaten Layak Anak di Masa Pandemi Covid-19 - Jadmiko Anom Husodo; Ummi A'zizah Zahroh (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2022)
Children are assets that have important potential for a nation. The realization of child protection has implications for the importance of providing special protection to fulfill children's rights. With the emergence of the large-scale phenomenon of Covid-19, the risks to safety, and the welfare of children as the most vulnerable group becomes much higher in a health emergency. The problem that will be analyzed in this research is how to implement child-friendly district policies during the Covid-19 pandemic with a case study of the Sukoharjo Regency. The research method used in this research is an empirical research method or socio-legal research with descriptive nature. The approach used in this research is a qualitative approach. The types and sources of legal materials used in this study include primary legal materials and secondary legal materials. By using the technique of collecting materials and data through field observation interviews, and document studies. This study will analyze the implementation of child-friendly district policies during the Covid-19 pandemic by studying the Sukoharjo District Regulation Number 12 of 2020 concerning Child-friendly Districts and the inhibiting factors faced by local governments and their efforts. Based on the results of the analysis, it was found that there are several problems that have not been met by Sukoharjo Regency as an autonomous region that has received an award as a child-friendly district, regarding the fulfillment of children's rights during the Covid-19 pandemic. In addition, there is still no implementing regulation to guarantee the fulfillment of children's rights during the Covid-19 pandemic. Because of these problems, it is expected to be able to provide special protection guarantees for children during the Covid-19 pandemic as a form of strengthening the implementation of child-friendly district policies.